Preliminary Studies on the Role of Trenches in Isolating Root Effect of Forest Trees Bordering Agricultural Crops - Singh, A; Daya, Rajbans (Annals of Arid Zone, 2016)
Technique ofÂ  "Trenching" was studied for reducing theinfluence of trees on agricultural crops under farm forestryprogramme at Soil Conservation Research Farm, Vasad. Yieldrif cotton and tobacco increased by 21 and 68% respectivelywhen lateral tree roots were cut-off by digging a trenchbetween two land-uses.